On the relation between Meridional Overturning Circulation and sea-level gradients in the Atlantic - Kienert, H.; Rahmstorf, S. (München : European Geopyhsical Union, 2012)
On the basis of model simulations, we examine what information on changes in the strength of the Atlantic Meridional Overturning Circulation (AMOC) can be extracted from associated changes in sea surface height (SSH), specifically from a broad Atlantic north–south gradient as has been suggested previously in the literature. Since a relation between AMOC and SSH changes can only be used as an AMOC diagnostic if it is valid independently of the specific forcing, we consider three different forcing types: increase of CO2 concentration, freshwater fluxes to the northern convection sites and the modification of Southern Ocean winds. We concentrate on a timescale of 100 yr. We find approximately linear and numerically similar relations between a sea-level difference within the Atlantic and the AMOC for freshwater as well as wind forcing. However, the relation is more complex in response to atmospheric CO2 increase, which precludes this sea-level difference as an AMOC diagnostic under climate change. Finally, we show qualitatively to what extent changes in SSH and AMOC strength, which are caused by simultaneous application of different forcings, correspond to the sum of the changes due to the individual forcings, a potential prerequisite for more complex SSH-based AMOC diagnostics